PENGARUH KUALITAS PRODUK, PROMOSI, HARGA TERHADAP KEPUASAN KONSUMEN KRECEK KRUPUK UYEL UD. SINAR HARAPAN - Putri, Yesi Darma (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose of this study is to analyze whether there isa significant effect between product quality, promotion and price variables simultaneously or partially on consumer satisfaction at UD Sinar Harapan. The approach used in this research is a quantitative approach and the type of research is causal relationship, the population in this study is all UD customers. Sinar Harapan which is unlimited in number, the sample is determined by 40 respondents who are taken using the sample accidental sampling technique, and the data analysis technique uses the classical assumption test, multiple linear regression, coefficient of determination, and hypothesis testing with the SPSSv25 tool. The results showed that product quality, promotion and price had a significant partial or simultaneous effect on consumer satisfaction at UD Sinar Harapan.